Sources of Inflation in Sub-Saharan Africa - Peiris, Shanaka; Barnichon, Regis (Washington, D.C. : International Monetary Fund, 2007)
This paper explores the sources of inflation in Sub-Saharan Africa by examining the relationship between inflation, the output gap, and the real money gap. Using heterogeneous panel cointegration estimation techniques, we estimate cointegrating vectors for the production function and the real money demand function to recover the structural output and money gaps for seventeen African countries. The central finding is that both gaps contain significant information regarding the evolution of inflation, albeit with a larger role played by the money gap. There is no significant evidence of asymmetry in the relationship.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet